Profil Career Adaptability Mahasiswa Bidikmisi Universitas Negeri Semarang - Saraswati, Sinta; Isrofin, Binti; N, Edwindha Prafitra (Universitas Ahmad Dahlan, 2017)
This study aimed to find out the profile of BidikmisiÂ students at Semarang State University (UNNES). This was a quantitative study with descriptive survey design. The subject of this study was 462 university students who were taken by simple random sampling technique. The data were collected by using career adaptability scale.The data were analyzed by using descriptive statistics. Based on the result of the analysis, it was found that the average profile of UNNESS Bidikmisi studentsâ€™ career adaptability was 51% and was categorized as high. The result of this study shows that the attempts in improving studentsâ€™ career adaptability by the lecturers, parents, and university counselors are needed